Self-powered smart patch promotes skin nerve regeneration and sensation restoration by delivering biological-electrical signals in program. (April 2022) - Tan, Min-hong; Xu, Xue-han; Yuan, Tie-jun; Hou, Xu; Wang, Jie; Jiang, Zhi-hong; Peng, Li-hua
Abstract: Skin wound is always accompanied with nerve destruction. Due to the limited clinical treatment option, loss of skin sensation with unsatisfactory nerve regeneration is remained to be a challenge for wound therapy. Endogenous mesenchymal stem cells (MSCs) based in situ regeneration, of which, MSCs recruited by chemokines and directed for neuronal differentiation by biological and electrical signals have been thought a novel strategy with potential to accelerate the nerve regeneration and sensory functions recovery. However, most current therapeutic systems usually deliver the chemokines, biological and electrical signals separately and statically, resulting in limited nerve regeneration and sensory functions recovery. Moreover, most of the devices for providing electrical signals need external energy input and complicated practice, leading to poor compliance in patients. To address these issues, we propose a self-powered smart patch (PRG-G-C) to provide chemokine and biological-electrical cues in program. PRG-G-C was composed of a flexible piezoelectric generator to supply electrical stimulation and a conductive gel, which served as the reservoir of chemokine and neural directing exosomes as well as the electrode to transfer electric cue. PRG-G-C was shown to efficiently accelerate rapid nerve regeneration and sensation restoration at the wound site within 23 days. This study demonstrates a proof-to-concept in organizing chemokine, neural directing biological-electrical heterogeneous cues within a self-powered smart patch for accelarating nerve regeneration and sensation restoration, possessing great potential in neural repair applications.